174 Benefits of a Self-Management Program for the Older Couple Living with Parkinson's Disease: A Pilot Study. (16th September 2019) - Lyons, Karen; Zajack, Alex; Greer, Melissa; Chaimoy, Holly; Dieckmann, Nathan; Carter, Julie
Abstract: Background: Although community-based self-management workshops have been found to benefit older adults with Parkinson's disease (PD), it is unclear if there could be added value for the couple if the spouse also participated. Methods: A quasi-experimental two-wave design (0 and seven week follow-up) was used to explore the effects of a self-management program on the health and relational outcomes of older adults with PD and their spouses in comparison to a wait-list control condition. Thirty nine couples were enrolled and completed the study (19 in the intervention group and 20 in the wait-list control). Results: Adjusting for baseline outcome values, spouses in the intervention group had significantly greater engagement in mental relaxation techniques (p < .001; d = 1.28) than those in the control condition at seven weeks. Additionally, moderate effect sizes were observed for increases in the mental relaxation (d = 0.44) and aerobic activity (d = 0.44) of older adults with PD and the strength-based activities of spouses (d = 0.33) in the intervention group. Small to moderate effects were observed for declines in the depressive symptoms of spouses (d = 0.29) and older adults with PD (d = 0.14) and care strain of spouses (d = 0.15) in the intervention group. Finally, perceptions of marital quality improved for older adults with PD (d = 0.46) and spouses (d = 0.41) and reports of protective buffering (i.e. hiding concerns) declined for older adults with PD (d = 0.24) and spouses (d = 0.33) in the intervention group compared to the wait-list control condition. Conclusion: Preliminary data showed promise for self-management programs benefiting couples living with Parkinson's disease. Although larger samples and randomized controlled trials are needed to establish the full benefit of such programs, greater attention to interventions for the older couple is warranted.